PENGARUH E-COMMERCE DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA PENGAMBILAN KEPUTUSAN DALAM BERWIRAUSAHA (Studi Kasus Pada Mahasiswa Akuntansi Angkatan 2017 di UNISMA, UM dan UMM) - Muhammad Faiz Labay Al Anshory; M. Cholid Mawardi; Siti Aminah Anwar (Universitas Islam Malang, 2022)
The purpose of this study was to determine the effect of e-commerce and the use of accounting information systems on decision-making in entrepreneurship. The population in this study were all students of the accounting study program, Faculty of Economics, Islamic University of Malang, the University of Muhammadiyah Malang, and State University of Malang, Class of 2017. The sample used was 90 samples that met the criteria for the research subject in 2021. The analytical method used was multiple regression equations, normality test, classical assumption test, descriptive statistical analysis, and hypothesis testing. The results of the study indicate that e-commerce and accounting information systems affect decision-making in entrepreneurship.Keywords: E-commerce, Accounting Information Systems, and Decision Making in Entrepreneurship